The Application of Coloured Petri Nets to Verification of Distributed Systems Specified by Message Sequence Charts - S. A. Chernenok (Труды Института системного программирования РАН, 2018)
The language of message sequence charts (MSC) is a popular scenario-based specification language used to describe the interaction of components in distributed systems. However, the methods for validation of MSC diagrams are underdeveloped. This paper describes a method for translation of MSC diagrams into coloured Petri nets (CPN). The method is applied to the property verification of these diagrams. The considered set of diagram elements is extended by the elements of UML sequence diagrams and compositional MSC diagrams. The properties of the resulting CPN are analyzed and verified using the known system CPN Tools and the CPN verifier based on the SPIN tool. The application of this method is illustrated with an example.